Elucidating tumour‐associated microglia/macrophage diversity along glioblastoma progression and under ACOD1 deficiency. Issue 17 (15th August 2022) - Pires‐Afonso, Yolanda; Muller, Arnaud; Grzyb, Kamil; Oudin, Anaïs; Yabo, Yahaya A.; Sousa, Carole; Scafidi, Andrea; Poli, Aurélie; Cosma, Antonio; Halder, Rashi; Coowar, Djalil; Golebiewska, Anna; et al.
Abstract : In glioblastoma (GBM), tumour‐associated microglia/macrophages (TAMs) represent the major cell type of the stromal compartment and contribute to tumour immune escape mechanisms. Thus, targeting TAMs is emerging as a promising strategy for immunotherapy. However, TAM heterogeneity and metabolic adaptation along GBM progression represent critical features for the design of effective TAM‐targeted therapies. Here, we comprehensively study the cellular and molecular changes of TAMs in the GL261 GBM mouse model, combining single‐cell RNA‐sequencing with flow cytometry and immunohistological analyses along GBM progression and in the absence of Acod1 (also known as Irg1 ), a key gene involved in the metabolic reprogramming of macrophages towards an anti‐inflammatory phenotype. Similarly to patients, we identify distinct TAM profiles, mainly based on their ontogeny, that reiterate the idea that microglia‐ and macrophage‐like cells show key transcriptional differences and dynamically adapt along GBM stages. Notably, we uncover decreased antigen‐presenting cell features and immune reactivity in TAMs along tumour progression that are instead enhanced in Acod1‐ deficient mice. Overall, our results provide insight into TAM heterogeneity and highlight a novel role for Acod1 in TAM adaptation during GBM progression. Abstract : By studying the education of tumour‐associated microglia/macrophages (TAMs) in the glioblastoma mouse model GL261 combining single‐cell RNA‐sequencing with immune‐profiling analyses, we show that resident microglia and monocytic‐derived macrophages within the tumour display key transcriptional differences and dynamically adapt along GBM stages. Specifically, TAMs exhibit decreased immune reactivity along tumour progression that is instead enhanced in Acod1‐ deficient mice.